Mental Health Resilience and Spiritual Well-Being: the Perspectives of Public Health and Islamic Psychology in Addressing the Shift in Life Priorities Among the Younger Generation - Naufal Faryreza Ryanta; Salsabila Ramadhani (Journal of Comprehensive Science, 2026)
The younger generation is currently experiencing significant shifts in life priorities as an adaptation to increasing economic pressures. Recent data indicate that approximately 70% of Generation Z and millennials prioritize work flexibility and self-reward as stress management strategies, while only about 40% continue to prioritize traditional commitments such as marriage or long-term asset ownership. This study aims to explore how Islamic spiritual values can synergize with public health sciences to formulate a balanced and sustainable well-being model. The identified research gap lies in the limited literature that simultaneously integrates contemporary phenomena—such as minimalist weddings and high self-reward consumption patterns—with the analysis of social determinants of health and Islamic psychology. The novelty of this study centers on examining the distinctive behavioral patterns of today’s youth, who display high efficiency in fulfilling traditional social obligations while demonstrating notable generosity in allocating resources toward mental health as a coping mechanism for modern life pressures. The method applied in this research is an integrative-narrative literature review, analyzing scholarly publications from the last five years (2021–2025). The findings reveal that financial anxiety, housing insecurity, and pressures associated with the digital era are primary determinants contributing to mental health vulnerabilities among young people. Furthermore, psychospiritual maturity through the concept of tawakkul (active surrender to God after maximal effort) functions as a protective factor capable of transforming feelings of hopelessness into psychological resilience. This synthesis concludes that holistic well-being can be achieved only through the integration of pro-youth public policy interventions and the activation of individual spiritual capital to regulate nafs ammarah (impulsive desires) in the face of uncertainty about the future.